(untitled) (Gaceta Técnica, 2022)
The present investigation consisted of surveying damage to reinforced concrete structures in the city of Nirgua, Yaracuy State, Venezuela. Through a preliminary inspection in which data of statistical interest was collected, failures or present damages were identified, classified and quantified, such as: cracks, fissures, concrete detachment, steel delamination, bleeding, stains, cracks. The survey was carried out in 2 zones, zone A called Sector Aire Libre, and zone B called Sector la Flor del Encanto E.B "Miguel Ángel Granado". The selection of the number of structures to inspect was determined by probabilistic sampling, considering preliminary investigations, in which a carbonation constant of approximately 8.32 mm/year 0.5 was determined. This study made it possible to determine if carbonation has caused damage to structures through corrosion.